The relation between adipose-derived stem cells and wound healing process - the review - Gruca, Dariusz; Zając, Marlena; Wróblewski, Wiktor; Borowiecka, Monika; Buksak, Dagmara (Journal of Education, Health and Sport, 2022)
Introduction and purpose: Wound healing is a process including complex overlapping stages requiring many components. Adipose tissue is an organ that is responsible for maintaining homeostasis through inflammatory responses, signal transmission, energy expenditure connected with different organs. Fat tissue is a rich and readily available source of multipotent stem cells. Adipose-derived stem cells (ADSCs) have the potential in tissue regeneration because of their self-renewal and ability to differentiate in various types of cells. This review discusses ADSCs in terms of basic knowledge, methods of acquisition, prospects for use in healthcare, focusing mainly on the potential application in the wound healing process. Brief description of the state of knowledge: The article contains current knowledge about biology, specific properties of adipose-derived stem cells and also shows the relationship to the wound healing process. The review presents research that points to the possibility of using ADSCs in future medicine. Conclusions: Adipose-derived stem cells may constitute a prominent role in tissue regeneration owing to the secretion of various cytokines, the ability to differentiate into multiple lineages, their immunomodulatory effects, and the ease of cell obtaining. Further studies are required to explore the accurate mechanism of ADSCs action and their long-term safety in clinical application. Stem cell therapy brings new hope for the repair of chronic and refractory wounds and skin defects.